﻿A. Y. Jackson, régionaliste québécois? - Gagnon, François-Marc (RACAR : Revue d'art canadienne / Canadian Art Review, 1994)
When visiting Québec, A. Y. Jackson was tempted by motifs which are traditionally attributed to the Québec regionalist school. The fact that he drew, on the suggestion of Clarence A. Gagnon, the illustrations of Adjutor Rivard's Chez Nous, a regionalist publication if there ever was one, demands explanation. The author’s thesis is that both the Québec regionalists (Clarence A. Gagnon above all) and A. Y. Jackson concurred in a touristic view of Québec. Their common enthusiasm for the Charlevoix region, to which Jackson succeeded in attracting Arthur Lismer, could be compared to Gauguin’s enthusiasm for Pont Aven. Both shared what D. MacCannell has called a “modernistic fascination for the premodern” and should be seen in the same “modernistic” perspective. Even the “direct” style adopted by Jackson seemed to substantiate this rapprochement.